(untitled) (Asian Journal of Social Science Studies, 2022)
With the birth of the art curriculum standard for compulsory education (2022 Edition), it can be found that the core quality of music discipline is more condensed into creative practice than before. This paper takes the second stage textbook of the human voice edition as an example to study the creative practice in the core literacy of music discipline, find out the problems existing in the core literacy of creative practice in primary school music textbooks, and put forward suggestions.